Artritis reumatoidea sistémica - SILICANI D. P, ARMANDO (2024)
Eigteen patients with systemic rheumatoid arthritis have been studied from the c/inically, radiologically, pathologically and inmunologically. The characteristic of systemic rheumatoid arthritis and systemic lupus erithemathosis are similar in sorne patients, however those with the first disease do have much more severe and destructive articular changes as well as higher titers of rheumatoid factors, on the other hand those with systemic lupus have compromise of the kidneys with much more frequency and a/so higher antinuclear antibodies titer in serum. Systemic rheumatoid arthritis would be a bridge between the classical rheumatoid disease and systemic lupus. Positive antinuclear antibodies were found in the serum of sixteen patients and just in fourteen ones in synovial fluids. lt was frecuently found more than one antinuclear antibody pattern. The pheriferal and the specklel antinuclear type more most frecuently found. The dilution of the serum and or synovial fluids led to changes in the antinuclear antibodies patterns in some of the cases. The mayority of the patients with systemic rheumatoid arthritis have higher titers of antinuc/ ear antibodies in serum than in sinovial fluids. The sygnificance of the anticuclear activity at the synovial level is still uncertain.